TMEM16 proteins: the long awaited calcium-activated chloride channels? - C.A. Flores; L.P. Cid; F.V. Sepúlveda; M.I. Niemeyer (Brazilian Journal of Medical and Biological Research, 2009)
Currents mediated by calcium-activated chloride channels (CaCCs), observed for the first time in Xenopus oocytes, have been recorded in many cells and tissues ranging from different types of neurons to epithelial and muscle cells. CaCCs play a role in the regulation of excitability in neurons including sensory receptors. In addition, they are crucial mediators of chloride movements in epithelial cells where their activity regulates electrolyte and fluid transport. The roles of CaCCs, particularly in epithelia, are briefly reviewed with emphasis on their function in secretory epithelia. The recent identification by three independent groups, using different strategies, of TMEM16A as the molecular counterpart of the CaCC is discussed. TMEM16A is part of a family that has 10 other members in mice. The discovery of the potential TMEM16 anion channel activity opens the way for the molecular investigation of the role of these anion channels in specific cells and in organ physiology and pathophysiology. The identification of TMEM16A protein as a CaCC chloride channel molecule represents a great triumph of scientific perseverance and ingenuity. The varied approaches used by the three independent research groups also augur well for the solidity of the discovery.